A Dynamic Evaluation of the Use of Natural Resources in Crop Rotation in Family Farming Production Units - Dayhanna Stephania Vargas; Juan Carlos Osorio; Juan José Bravo (Resources)
A total of 35.4% of the earth’s surface is used for agriculture, and 32.7% of it for crops. Agricultural activity uses 70% of the world’s freshwater, and due to the intensive use of agrochemical inputs and energy, a high percentage of greenhouse gas emissions, pollution, and waste are generated. With the increase in population and fluctuating consumption trends, it is necessary to increase crop production and productivity to meet present and future demands. A relevant factor for the analysis of the production of agricultural goods is the size of the productive unit since about 84% is less than 2 ha in size and distributed over 12% of arable land; however, it is important to highlight other factors, such as the availability of family labour, crop diversification and the development of other agricultural activities that have a lower use of insecticides, pesticides, and chemical fertilisers compared to industrial crops. Therefore, food is produced, providing social and ecological benefits. Thus, a dynamic simulation is presented to evaluate the use of natural resources in developing different rotations of transient and permanent crops in a municipality in Colombia. This study assesses the impact on land use, soil degradation due to crop development, and the total water footprint associated with each rotation.